Kontribusi Bank Wakaf Mikro Pada Akses Keuangan Syariah: Potensi Pengembangan UMKM Kota Kediri - Adhi Purba, Ilyas (Fakultas Syariah dan Ekonomi Islam, 2023)
Bank Wakaf Mikro is a sharia financial institution that helps developt the micro business sector. Kediri City has two Bank Wakaf Mikro wich have been inaugurated. The purpose of this study to show the contribution of Bank Wakaf Mikro in sharia financial and explore the potential for UMKM with existence Bank Wakaf Mikro in Kediri city. This research is qualitative type that obtains secondary data. The analysis with descriptive approach based on associated with existing theory. The results of this study explain that Bank Wakaf Mikro have contribution to access sharia financial in terms of literacy through pre-financial provision and halaqah mingguan also the inclusion through qardhul hasan financing. The potential of development UMKM in Kediri trough projections of community that get benefited from financing